2006
DOI: 10.1111/j.1365-2354.2006.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

What women want: convenient appointment times for cervical screening tests

Abstract: Little is known about women's preferred appointment times for cervical screening tests. Data from a postal questionnaire survey were used to compare preferred appointment times with those given. Although 33.4%[95% confidence intervals (CI) 31.8%-35.0%] of respondents received appointments between 10h00 and 11h55, only 17.0% (95% CI 15.3%-18.7%) wanted an appointment at that time. Nineteen per cent (95% CI 17.4%-21.0%) of respondents wanted appointments between 18h00 and 20h00, but only 4.4% (95% CI 3.7%-5.1%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 5 publications
3
18
0
Order By: Relevance
“…For example, some patients may be willing to see any available doctor to minimize their wait for an appointment, whereas some other patients may prefer to wait until a slot becomes available with their PCPs (thereby preserving continuity). Some patients are able to visit the clinic only within a short time window because of job-related constraints or personal schedules, whereas others can be quite flexible (Jennings et al 2005;Olowokure et al 2006). Time and physician preferences may change over time because of changes in work schedule, marital status, and family size.…”
Section: The Appointment Booking Problemmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, some patients may be willing to see any available doctor to minimize their wait for an appointment, whereas some other patients may prefer to wait until a slot becomes available with their PCPs (thereby preserving continuity). Some patients are able to visit the clinic only within a short time window because of job-related constraints or personal schedules, whereas others can be quite flexible (Jennings et al 2005;Olowokure et al 2006). Time and physician preferences may change over time because of changes in work schedule, marital status, and family size.…”
Section: The Appointment Booking Problemmentioning
confidence: 97%
“…Instead, they typically wish to book an appointment with a doctor of choice at a convenient time of day that fits their schedules (Jennings et al 2005;Olowokure et al 2006). Patients' preferences may also depend on urgency of their medical needs and the schedule of appointments they hold with other clinics/providers because patients generally want to minimize number of trips to the clinic/health system.…”
Section: Patient Preferencesmentioning
confidence: 98%
“…9,[13][14][15] In addition, the health professionals suggested that population mobility, particularly in young women, might be a problem, and some thought that structural factors such as GP incentivisation and the change in the age of first screening might contribute to declining participation in this group; barriers that women themselves would not necessarily be aware of. For some women, the decision not to attend screening was informed; they perceived that the costs outweighed the benefits or they were not sexually active.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested a cohort effect, hypothesising that nonattendance reflects broader social disillusionment. 5,6 Others have suggested that young women experience more barriers to attendance, such as embarrassment, 7 lower perceived risk, 8 difficulties with appointment times, 9 or not being registered with a GP.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to cervical screening include demographic, socioeconomic, psychological and cultural factors 9–18. Inaccuracies of patients' addresses and of medical records19–21 as well as inconvenient appointment times2123 could also reduce participation.…”
Section: Introductionmentioning
confidence: 99%